Penerapan Pembelajaran Agama Buddha Berbasis Kearifan dan Budaya Lokal di Sekolah Minggu Buddha (SMB) Adhicitta Suruh, Tengaran, dan Susukan - Andanti, Maria (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
This study was the first of the two-cycled action research. This study aimed at building teachers’ understanding of integrating local wisdom and culture content with Buddhism at Adhicitta Buddhist Sunday School, Suruh, Tengaran, and Susukan, as the basis of the implementation of local wisdom and culture-based Buddhist learning. The   first cycle of action research consisted of three stages, Look, Think, and Act. The data gathering technique employed interview, observation, and documentation. The data was analyzed through data condensation, data display, and drawing and verification conclusions. The results showed that the teachers at Adhicitta Buddhist Sunday School, Suruh, Tengaran, and Susukan had not completely understood how to integrate local wisdom and culture content with Buddhism. The human resources limitation and the high demand of the Buddhist Sunday School Curriculum contributed as the main factors of the teachers’ poor understanding. Based on the evaluation of the latest step of Act, the next cycle focused on the intensive training towards the teachers at Adhicitta Buddhist Sunday School, Suruh, Tengaran, and Susukan in designing local wisdom and culture-based Buddhist lesson plans.